BIS(2,2,2-TRIFLUOROETHYL)(2-CYANOETHYL) PHOSPHATE – A NEW URANIUM EXTRAGENT - A.M. Nalibayeva,; Bishimbayeva G.K,; Saidullayeva S.A. ,; Verhoturova S.I,; Arbuzova S.N.,; Gusarova N.K, (Academic Scientific Journal of Chemistry, 2020)
Organophosphate compounds are widely used in industrial hydrometallurgical processes as extractants and complexones of non-ferrous, noble, rare-earth metals and transuranic elements. Among these compounds, organic phosphates occupy a special place, as they allow for the extraction processes with good selectivity and efficiency. However, a significant drawback of known organic phosphates is their low extraction capacity, as well as rather good solubility in water and their hydrolysability in aqueous acidic solutions, which leads to both loss of the extractant and contamination of the extracted metal with organophosphorus compounds. Therefore, the search and development of new uranium effective extractants is an important task for the development of modern hydrometallurgical processes.This report describes the successful use of available bis(2,2,2-trifluoroethyl)(2-cyanoethyl)phosphate, which is easily obtained from bis(2,2,2-trifluoroethyl) chlorophosphate and 3-hydroxypropanonitrile in the pyridine/diethyl ether system as an extractant of uranium from uranium-containing acid solutions. For this functional phosphate containing a cyano group, one should expect a synergistic effect of the extraction properties of the phosphates themselves, as well as of the known extractants - contribute to an increase in its incombustibility.The purpose of this research is to develop the optimal conditions for the scaled synthesis of bis(2,2,2-trifluoroethyl)(2-cyanoethyl)phosphate, to accumulate its enlarged batch and to study the extraction properties in the production process of uranium extraction from uranium-containing sulfate and nitric acid solutions.The research results showed that bis(2,2,2-trifluoroethyl)(2-cyanoethyl) phosphate, easily obtained from the available bis(2,2,2-trifluoroethyl) chlorophosphate and 3-hydroxypropanonitrile in the pyridine/diethyl ether system, exhibits pronounced extraction properties with respect to uranium. Thus, the use of this extractant in the production of the extraction of uranium from uranium-containing nitric acid or sulfuric acid solutions was 20.7% and 18.7%; the content of uranium in the extractant was 63.9 g/dm3 and 49. 7 g/dm3 , respectively.Positive results were also obtained when studying the synergistic properties of the new extractant and the traditional - bis(2-ethylhexyl) phosphate. Using a mixture of these extractants (their weight ratio was 1:1.2) allows you to extract 57% of uranium from the uranium sulphate solution. This is 9% more than in a similar process using only bis(2-ethylhexyl) phosphate as an extractant. The use of bis(2,2,2-trifluoroethyl)(2-cyanoethyl) phosphate as a new extractant makes it possible to extract up to 20.7% of uranium from technological nitrate or sulphate of uranium-containing solutions. With the combined use of bis(2,2,2-trifluoroethyl)(2-cyanoethyl) phosphate and the known extractant bis(2-ethylhexyl) phosphate in this process, a synergistic effect is observed, which increases the efficiency of uranium extraction and improves the technological indicators of extraction.The extractantbis(2,2,2- trifluoroethyl)(2-cyanoethyl) phosphate works more efficiently in nitric acid solutions than in sulphate